Law for Authentic Secular Sanctity (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This article examines the concept of secular sacrality in law, tracing the numinous roots of the legal order and the transition from natural law to positivism. It explores how sacrality, traditionally linked to religion, transforms into a secular value founded on human dignity and the inviolability of life. By referencing Durkheim, Otto, Girard, Benjamin, and Agamben, the article highlights the tension between law’s regulatory function and the inherent violence in managing the sacred. The analysis concludes with reflections on the right to die and the protection of individual autonomy, ultimately ensuring a truly just, equitable society that respects human dignity.
Keywords: Secular sanctity; natural law; legal positivism; sacred violence; individual autonomy